Study on Operating Modes of a Biofuel Diesel Engine - V. A. Likhanov; O. P. Lopatin (Advanced Engineering Research, 2025)
Introduction. Modern research aimed at reducing emissions of harmful substances resulting from the operation of diesel engines using alternative fuels emphasizes their importance and relevance. This topic is becoming increasingly significant in the context of global environmental changes. The development and implementation of alternative energy sources not only contribute to improving air quality, but also help reduce dependence on fossil fuels. Therefore, it is important to continue investing in research and new technologies that will provide for cleaner and more efficient use of resources. There are numerous such studies, specifically, theoretical ones, conducted in European and Asian countries. However, there are practically no experimental works devoted to hemispherical combustion chambers of Russian diesel engines, whose rotation speed, compression ratio and other design parameters differ significantly from similar characteristics described in known studies. In addition, there are practically no experiments devoted to the combustion process of Russian diesel engines with an undivided hemispherical combustion chamber in the piston, which determines the complexity of the volumetric-film mixing process. The research objective is an experimental study of the power and economic indicators, parameters of the combustion process of a diesel engine with an undivided hemispherical combustion chamber in the piston, running on ethanol and rapeseed oil (RO). The study is aimed at establishing dependences showing the effect of various engine operating modes on the specified indicators in order to determine their numerical characteristics.Materials and Methods. The diesel engine was started using rapeseed oil, after which the ethanol supply was switched on, replacing the rapeseed oil until the set optimum value was reached. The increase in the operating load mode was provided through regulating the ethanol supply. An additional high-pressure fuel pump (HPFP) 2UTNM was installed to supply rapeseed oil, and ethanol was supplied through the standard fuel supply system.Results. The indicators of the combustion process of a diesel engine running on ethanol and rapeseed oil differ from its regular diesel engine. When working with ethanol and rapeseed oil, an increase in the ignition delay period is noted, which affects the “rigidity” of the combustion process and results in a growth of Pz value. These factors are most likely the main limitations for the use of ethanol by direct injection. One of the solutions to this problem, proposed in this paper, is the use of ignition (pilot) rapeseed oil, which makes it possible to adjust parameters of the combustion process through controlling the amount of ignition fuel supply.Discussion and Conclusion. The results of the conducted experimental study confirm the possibility of complete replacement of petroleum motor fuel in a diesel engine with an undivided hemispherical combustion chamber in the piston with an alternative (renewable) fuel. This undoubtedly solves important issues of environmental safety of diesel engines. The research results may be useful both to scientists working on this topic, and to engineers and technicians in the machine-building industry.